Does Prepregnancy Weight or Maternal BMI at Betamethasone Administration Impact Late Preterm Respiratory Morbidity? - Bicocca, Matthew J.; Blackwell, Sean C.; Sibai, Baha M. (American Journal of Perinatology, 2020)
Objective We sought to determine if maternal prepregnancy body mass index (BMI) is a risk factor for neonatal respiratory morbidity and to determine if increasing BMI decreased the efficacy of betamethasone (BMZ).Study Design This was a secondary analysis of the Antenatal Late Preterm Steroids trial, double-blind, randomized controlled trial involving 2,831 women between 340/7 and 365/7 weeks who received BMZ or a matching placebo. We compared the rate of neonatal respiratory morbidity among prepregnancy BMI classes in both the placebo and treatment groups. We also stratified the treatment effect by maternal BMI at the time of delivery.Results A total of 2,822 women were identified with maternal weight recorded at delivery; 2,740 women also had self-reported prepregnancy weight available. When stratified by prepregnancy BMI class, there was no difference in neonatal respiratory morbidity in the BMZ or in placebo groups. When analyzed by BMI at delivery, there was no difference in the rate of neonatal respiratory morbidity, and BMI was not a predictor of treatment response (odds ratio = 1.00, 95% confidence interval = 0.99–1.02).Conclusion Maternal prepregnancy BMI is not associated with late preterm neonatal respiratory morbidity. Maternal obesity does not decrease the efficacy of BMZ for preventing late preterm neonatal respiratory morbidity.
Keywords: obesity; late preterm; fetal; lung; betamethasone; respiratory